Exploring Structural, Magnetic, and Electric Transport Properties of Sol–Gel Derived Nd0.65Ca0.35MnO3 - Bhupendra Singh; Gaurav Joshi; Sudha Tomar; D. S. Raghav; Raj Kumar; Upendra Kumar; Lalit Kumar (Advances in Condensed Matter Physics)
This paper investigates the phase separation phenomena in low bandwidth manganites, such as Nd1-xCaxMnO3, focusing on the nanoscale effects. Specifically, it aims to understand the competing phase tendencies concerning particle size in the prototypical phase-separated compound Nd0.65Ca0.35MnO3 (NCMO). Nanosized material was synthesized through sintering sol–gel derived powders at a temperature of 900°C. Using the Rietveld refinement technique, the structure of the NCMO was investigated. It was found that NCMO has an orthorhombic shape with the Pnma spatial group. Mn2p and Mn2s core-level X-ray photoemission spectroscopy confirms that Mn has +3, +4 ions coexist in the intended ratio. The transition from paramagnetic (PM) to ferromagnetic (FM) states is shown by magnetization measurements performed at H = 100 Oe. Observations of note include the disparity between zero-field cooled (ZFC) and field cooled warming (FCW) magnetization, indicating a glassy behavior at lower temperatures, and the hysteresis loop between cooling and warming cycle in the presence of field magnetization. Isothermal magnetization loop analysis confirms the dominance of the antiferromagnetic (AFM) component at higher magnetic fields. However, the resistivity versus temperature data does not reveal an insulator–metal transition (IMT). Instead, the PM state in the sample shows conduction via variable range hopping.